ANALYSIS OF FACTORS AFFECTING COMPANY USING DERIVATIVES - Sriwati Sriwati (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This study aims to determine the factors that influence companies in using derivatives. In this study, the factors studied were the cost of debt, foreign sales, risk management, and corporate governance on the company's decision to use derivatives. The analytical method used in this research is logistic regression analysis using the Statistical Product and Services Solutions software. A total of 60 samples were used in this study, which were 20 companies included in the Corporate Governance Perception Index survey from 2016 to 2018. The Corporate Governance Perception Index survey is a survey conducted by the Indonesian Institute for Corporate Governance. The results of this study indicate that the cost of debt variable has a significant effect on the decision to use derivatives by the company. The corporate governance variable also has a significant effect on the decision to use derivatives by the company. The foreign sales variable in this study does not have a significant effect on the decision to use derivatives by companies. The risk management variable does not have a significant effect on the decision to use derivatives by the company. In this study, there are also control variables, namely firm size and return on assets. In this study, the firm size variable does not have a significant effect on the decision to use derivatives by the company. Meanwhile, the return on assets variable has a significant effect on the decision to use derivatives by the company.